The New Career Paradigm of Indonesian Youth: An Analysis of Career Preference Shifts in the Digital Era - Susanti, Nova; Anggreiny, Nila; Khan, Zafar (The Indonesian Institute of Science and Technology Research, 2025)
This study examines the shifting career preferences of Indonesian youth, who are increasingly moving from formal employment toward informal and flexible work models. Using a mixed-methods approach that integrates national statistics from Badan Pusat Statistik (BPS), regional survey data, and literature analysis, the study identifies key socio-economic and cultural drivers behind this transition. Findings are organized into three themes: the growing prevalence of informal work among young people, rising demand for flexibility in income generation and work arrangements, and the broader socio-economic implications for stability, skills development, and long-term employability. The study concludes that this shift reflects both structural labour-market changes and evolving youth aspirations. It recommends strengthening policy support for youth entrepreneurship, integrating flexible-work competencies into education and training, and improving social protection mechanisms to ensure sustainable participation in an increasingly informal economy.